ANALISIS GEOGRAPHIC INFORMATION SYSTEM FAKTOR RISIKO BAYI BERAT BADAN LAHIR RENDAH (BBLR) PADA IBU HAMIL DENGAN MALARIA: STUDI KASUS - Heni Voni Rerey; Ika Wijayanti; Andreas Ayomi (Media Penelitian dan Pengembangan Kesehatan, 2024)
Papua has the highest rate of malaria cases among all provinces in Indonesia. Malaria is a scourge, especially among vulnerable groups, including pregnant women. Pregnant women with malaria increase the risk of giving birth to Low Birth Weight (LBW). This study aimed to analyze geographic information system risk factors for LBW in pregnant women with malaria. This research method was observational analytics using a matched case-control design. The study encompassed pregnant women residing in the Sentani health center working area, who were both afflicted with and unaffected by malaria, and sought outpatient care at the health center. With a population of 104 pregnant woman, and the sample used was the Total sampling technique. This study found that the distribution of LBW cases tends to increase if there are many malaria incidents in the area. The distribution pattern of malaria cases shows a tendency to gather in areas with high rainfall, areas with low air humidity and areas with high air temperatures, namely Nolokla and Asei Villages. To maintain the health of mothers and babies and avoid possible risks, it is necessary to increase supervision and vigilance in the months where the intensity of rain increases, namely from November to March, where rainfall is also related to humidity and temperature so that it affects the sustainability of mosquito larvae habitat